'Widening Access' to higher education: the reproduction of university hierarchies through policy enactment. Issue 1 (2nd January 2019) - Evans, Ceryn; Rees, Gareth; Taylor, Chris; Wright, Caroline
Abstract: Patterns of participation in higher education (HE) in the UK, as elsewhere, have been marked by social inequalities for decades. UK Governments have responded with a plethora of policies and agendas aimed at addressing this broad social issue. However, little is known about how higher education institutions (HEIs) interpret and 'enact' these policies in relation to institution-specific contexts. Drawing on concepts from policy sociology this paper examines how HEIs in one nation state, Wales, enact its Government's policy on 'widening access' to higher education. Interviews with a range of 'policy actors' along with analyses of institutional 'widening access' policy documents, reveal divergences between HEIs in how this policy agenda is interpreted and delivered. These differences reflect institution-specific contexts – not least their internal politics and assumptions about the type of students they admit, but also their interests and priorities in relation to their positions within a global, marketised, HE system. The implications of this for the reproduction of university hierarchies in the UK, as well as social inequalities more generally are brought to the fore.